Annals of clinical psychiatry ([Elsevier], 1989)
" ... publishes high-quality clinical articles that focus on the advancement of patient care. Contributions furnish professionals and students with a continuing medical perspective on their discipline, addressing problems and concerns that arise in clinical practice as well as their potential solutions."